Ceramic hollow microsphere composite material and preparation method thereof
Patent Information
- Application Number
- CN202611149683.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]然而,上述现有空心微球在实际应用中均存在各自的技术缺陷,限制了其在高端复合材料领域的进一步推广
1.解决了传统微球耐压不足、结构易失效的缺陷,大幅提升材料高压服役稳定性,本发明选用陶瓷空心微球,克服了空心玻璃微球抗压强度不足 30 MPa、高压下易压溃失效,以及聚合物微球强度低、无法承力的缺陷。同时相较于普通单一组分陶瓷微球,本发明通过材质优选与参数限定,在保证极低密度的前提下保留超高结构稳定性,应用于深海高压、深井固井等严苛工况时,可有效避免微球坍塌、复合材料轻质特性失效的问题,显著提升材料承压服役寿命。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, specifically relating to a ceramic hollow microsphere composite material and its preparation method. Background Technology
[0002] Hollow microspheres, due to their excellent properties such as lightweight, high strength, thermal insulation, and low dielectric constant, have broad application prospects in high-end technology fields such as aerospace, deep-sea exploration, oil drilling, automotive lightweighting, and 5G communication. Based on the different materials used, existing hollow microspheres are mainly divided into three categories: hollow glass microspheres, hollow polymer microspheres, and hollow ceramic microspheres.
[0003] However, the aforementioned existing hollow microspheres all have their own technical defects in practical applications, which limits their further promotion in the field of high-end composite materials.
[0004] First, while hollow glass microspheres are low-cost and have controllable density, their compressive strength is typically limited (generally not exceeding 30 MPa). Under high-pressure environments (such as deep-sea or deep-well conditions), they are prone to crushing, causing the composite material to lose the lightweight advantage of its hollow structure and even leading to a sharp decline in the overall mechanical properties of the material. Furthermore, the surface of hollow glass microspheres is rich in silanol groups, which are highly polar. When combined with most organic matrix materials, they exhibit poor dispersibility and weak interfacial bonding, making it difficult to form high-quality composite materials.
[0005] Secondly, although hollow polymer microspheres have lower density and better compatibility with organic matrices, they have poor heat resistance, with thermal decomposition temperatures typically below 250°C. This fails to meet the processing temperature requirements of high-temperature engineering plastics and makes it difficult to maintain structural stability in high-temperature curing or high-temperature service environments. Furthermore, polymer microspheres generally have low compressive strength, making them unsuitable for load-bearing structural components.
[0006] Third, while some existing single-component ceramic microspheres have improved heat resistance and compressive strength, they often suffer from problems such as high density, complex preparation processes, and excessively high costs. More importantly, ceramic microspheres made of different materials (such as alumina, zirconium oxide, mullite, and aluminum silicate) exhibit significant differences in surface properties, mechanical properties, and chemical stability. Current technologies lack a systematic understanding of the compatibility of hollow ceramic microspheres with different matrix environments, leading to blind selection in practical applications and hindering the full realization of the performance advantages of hollow ceramic microspheres.
[0007] Fourth, in the actual preparation of composite materials, the addition of hollow microspheres often brings a series of processing and service performance problems. For example, during high-temperature molding, the thermal expansion of gas or moisture trapped inside the microspheres may cause bubbles to form inside the composite material; excessive density differences between the microspheres and the matrix may lead to uneven dispersion, floating, or settling; and mismatch between the surface properties of the microspheres and the matrix may lead to interfacial debonding and performance degradation. These problems have not yet been systematically solved in the existing technology.
[0008] Ceramic hollow microspheres, with their inherent properties as inorganic non-metallic materials—high strength, high heat resistance, low water absorption, and chemical stability—have a natural advantage in solving the aforementioned problems. However, current technology lacks a systematic technical solution for selecting ceramic hollow microspheres of different materials for different matrix systems. Therefore, developing a composite material with ceramic hollow microspheres as the sole microsphere filler, and selecting the most suitable type of ceramic hollow microspheres according to the characteristics of different matrix materials, can simultaneously meet multiple performance requirements such as lightweight, high strength, high temperature resistance, high pressure resistance, and low water absorption. This is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0009] To address the aforementioned problems, the main objective of this invention is to design a ceramic hollow microsphere composite material and its preparation method.
[0010] To achieve the above objectives, the present invention adopts the following technical solution: A ceramic hollow microsphere composite material includes a matrix material and ceramic hollow microspheres. The ceramic hollow microspheres are uniformly dispersed and mixed in the matrix material. The ceramic hollow microspheres are one or a combination of alumina ceramic hollow microspheres, zirconia ceramic hollow microspheres, mullite ceramic hollow microspheres, and aluminum silicate ceramic hollow microspheres. The matrix material is any one of polyamide resin, epoxy resin, or cement. The particle size D50 of the ceramic hollow microspheres is 10-100 μm.
[0011] As a further description of the present invention, when the matrix material is polyamide resin, it comprises 18-22 parts of ceramic hollow microspheres, 0.5-2 parts of coupling agent, and 0.1-1 parts of antioxidant per 100 parts by weight of polyamide resin; the ceramic hollow microspheres are mullite ceramic hollow microspheres or aluminosilicate ceramic hollow microspheres.
[0012] As a further description of the present invention, when the matrix material is epoxy resin, it comprises 33-38 parts of ceramic hollow microspheres and 2-5 parts of curing agent per 100 parts by weight of epoxy resin; the ceramic hollow microspheres are alumina ceramic hollow microspheres, zirconia ceramic hollow microspheres or a combination thereof.
[0013] As a further description of the present invention, when the matrix material is cement, it comprises 22-28 parts of ceramic hollow microspheres, 0.5-1.5 parts of dispersant, 0.5-2 parts of water loss reducing agent, and 0.1-1 parts of retarder per 100 parts by weight of cement; wherein the ceramic hollow microspheres are mullite or aluminosilicate ceramic hollow microspheres.
[0014] As a further description of the present invention, the ceramic hollow microspheres are surface modified by a coupling agent, which is a silane coupling agent, a titanate coupling agent, or an aluminate coupling agent.
[0015] As a further description of the present invention, the polyamide resin is PA66, PA12 or PA46; the epoxy resin is bisphenol A type epoxy resin, bisphenol F type epoxy resin or phenolic type epoxy resin; the cement is G grade oil well cement, H grade oil well cement or silicate cement.
[0016] The method for preparing ceramic hollow microsphere composite materials based on this application includes the following steps: Step 1: Surface modification treatment of ceramic hollow microspheres; Step 2: Mix the modified ceramic hollow microspheres with the matrix material and additives evenly; Step 3: Depending on the type of base material, molding is carried out by melt blending injection molding, pouring curing, or water mixing and curing.
[0017] As a further description of the present invention, when the matrix material is polyamide resin, it is melt-blended using a twin-screw extruder with a barrel temperature of 200-300°C, and ceramic hollow microspheres are added by side feeding for injection molding; when the matrix material is epoxy resin, it is cast-molded and cured at room temperature to 120°C; when the matrix material is cement, water is added at a water-cement ratio of 0.3-0.6, stirred, and then molded for curing.
[0018] As a further description of the present invention, the surface modification treatment in step one involves preparing a 1-4 wt% coupling agent ethanol aqueous solution, soaking and stirring the ceramic hollow microspheres for 15-25 min, and then drying them at 90-110°C for 1.5-2.5 h.
[0019] Compared with the prior art, the technical advantages of the present invention are as follows: 1. This invention addresses the shortcomings of traditional microspheres, such as insufficient pressure resistance and susceptibility to structural failure, significantly improving the material's stability under high pressure. It utilizes hollow ceramic microspheres, overcoming the limitations of hollow glass microspheres (compressive strength less than 30 MPa, prone to crushing under high pressure) and polymer microspheres (low strength, unable to bear loads). Furthermore, compared to ordinary single-component ceramic microspheres, this invention, through material selection and parameter limitation, maintains ultra-high structural stability while ensuring extremely low density. When applied to harsh conditions such as deep-sea high pressure and deep well cementing, it effectively avoids microsphere collapse and the failure of the lightweight properties of composite materials, significantly extending the material's pressure-bearing service life.
[0020] 2. Existing technologies lack a compatibility system for different matrices and ceramic microspheres, resulting in problems such as chaotic material selection and low performance utilization. This invention establishes a targeted matching system: mullite and alumina silicate hollow microspheres are preferred for the polyamide matrix; alumina and zirconia hollow microspheres are preferred for the epoxy resin matrix; and mullite and alumina silicate hollow microspheres are suitable for the cement matrix. Combined with a surface modification process using a coupling agent, this effectively improves the mismatch between the surface polarity of the ceramic microspheres and the compatibility with the matrix, eliminates defects such as interfacial debonding and weak bonding, and maximizes the mechanical, heat-resistant, and stable performance advantages of ceramic microspheres made of different materials.
[0021] 3. Solved the common molding problems of hollow microsphere composite systems. For polyamide injection molding systems, it avoids the problems of air bubbles and warping caused by gas generation from microspheres, achieving defect-free molding of products; for epoxy resin systems, the closed-cell structure of microspheres combined with optimized formulation results in extremely low water absorption and buoyancy loss rates, structural stability under high pressure holding, and excellent water-proof and seepage-proof performance; for cement systems, the dispersion is optimized through additive compounding, solving the problems of microsphere floating, settling, and uneven dispersion, improving the overall uniformity and construction stability of cement-based composite materials.
[0022] 4. It overcomes the limitations of traditional microsphere composite materials, such as low temperature resistance, pressure difference resistance, weak stability, and limited applicability. The material simultaneously possesses multiple advantages, including lightweight, high strength, high temperature resistance, high pressure resistance, low water absorption, and good chemical stability. It can be precisely adapted to high-end and demanding applications such as lightweight automotive structural components, deep-sea pressure-resistant buoyancy components at depths of 10,000 meters, deep-sea oil and gas extraction equipment, and high-pressure cementing sheaths for deep wells. This solves the industry problem of existing materials being unable to meet the performance requirements of multiple extreme working conditions, demonstrating extremely high engineering application value and industrialization prospects.
[0023] 5. Using ceramic hollow microspheres as the only microsphere filler eliminates the need for mixed systems with multiple fillers. The formula is simple and the components are controllable. At the same time, it is matched with exclusive molding processes for different matrices such as resin and cement, which has strong process compatibility and high production stability. It avoids the problems of complex composition, difficult process and high cost of traditional composite systems, and is convenient for large-scale industrial production. Detailed Implementation
[0024] The present invention will now be described in detail: This application provides a ceramic hollow microsphere composite material, mainly composed of a matrix material and ceramic hollow microspheres. The ceramic hollow microspheres are uniformly dispersed and mixed in the matrix material. The ceramic hollow microspheres are one or a combination of alumina ceramic hollow microspheres, zirconia ceramic hollow microspheres, mullite ceramic hollow microspheres, and aluminum silicate ceramic hollow microspheres. The matrix material is any one of polyamide resin, epoxy resin, or cement. The particle size D50 of the ceramic hollow microspheres is 10-100 μm.
[0025] When polyamide resin is selected as the matrix material, it contains 18-22 parts of ceramic hollow microspheres, 0.5-2 parts of coupling agent, and 0.1-1 parts of antioxidant per 100 parts by weight of polyamide resin; the ceramic hollow microspheres are mullite ceramic hollow microspheres or aluminosilicate ceramic hollow microspheres.
[0026] When epoxy resin is selected as the matrix material, it contains 33-38 parts of ceramic hollow microspheres and 2-5 parts of curing agent per 100 parts by weight of epoxy resin; the ceramic hollow microspheres are alumina ceramic hollow microspheres, zirconia ceramic hollow microspheres or a combination thereof.
[0027] When cement is selected as the matrix material, it contains 22-28 parts of ceramic hollow microspheres, 0.5-1.5 parts of dispersant, 0.5-2 parts of water loss reducing agent, and 0.1-1 parts of retarder per 100 parts by weight of cement; the ceramic hollow microspheres are mullite or aluminosilicate ceramic hollow microspheres.
[0028] The coupling agent is a silane coupling agent, titanate coupling agent, or aluminate coupling agent. The polyamide resin is PA66, PA12, or PA46; the epoxy resin is bisphenol A type epoxy resin, bisphenol F type epoxy resin, or phenolic type epoxy resin; and the cement is G-grade oil well cement, H-grade oil well cement, or silicate cement.
[0029] The method for preparing ceramic hollow microsphere composite materials based on this application includes the following steps: Step 1: Surface modification treatment of ceramic hollow microspheres; Step 2: Mix the modified ceramic hollow microspheres with the matrix material and additives evenly; Step 3: Depending on the type of base material, molding is carried out by melt blending injection molding, pouring curing, or water mixing and curing.
[0030] When the matrix material is polyamide resin, a twin-screw extruder is used for melt blending, the barrel temperature is 200-300℃, and ceramic hollow microspheres are added by side feeding for injection molding; when the matrix material is epoxy resin, casting molding is used and cured at room temperature to 120℃; when the matrix material is cement, water is added at a water-cement ratio of 0.3-0.6, stirred, and then injected into the mold for curing.
[0031] The surface modification treatment in step one involves preparing a 1-4 wt% coupling agent ethanol aqueous solution, soaking and stirring the ceramic hollow microspheres for 15-25 min, and then drying them at 90-110℃ for 1.5-2.5 h. Example 1
[0032] The ceramic hollow microsphere composite material was prepared using polyamide resin (PA66), mullite ceramic hollow microspheres, coupling agent, and antioxidant. The preparation steps are as follows: Step 1: Prepare a 2% silane coupling agent ethanol aqueous solution, soak and stir the microspheres for 20 min, dry at 100℃ for 2 h, and perform surface modification treatment; Step 2: Mix PA66 and antioxidant and stir thoroughly until homogeneous; Step 3: At an environment of 240-270℃, the modified mullite ceramic microspheres are added laterally at a uniform speed of 300 r / min, and then melt-blended and granulated. Step 4: Raise the mold temperature to 80℃ and prepare the molded product at an injection temperature of 250-275℃.
[0033] Based on the above preparation method, test strips were prepared by selecting different raw material ratios. The specific experimental ratios and performance data are as follows (PA66=100 parts by weight). Based on the above experimental data, it can be seen that adding ceramic hollow microspheres to polyamide resin as a matrix can achieve a weight reduction of 30% to 40%. At the same time, the tensile modulus and heat distortion temperature are significantly better than those of pure polyamide substrate, achieving the effects of lightweight, high rigidity and high temperature resistance. Moreover, the samples are free of defects such as bubbles and warping, with a high yield rate. It is fully compatible with composite materials that combine lightweight, mechanical heat resistance and good processing performance, such as lightweight injection molded parts for automobiles. Example 2
[0034] The ceramic hollow microsphere composite material was prepared using bisphenol A type epoxy resin, alumina-zirconia composite ceramic hollow microspheres, and alicyclic amine curing agent. The preparation steps are as follows: Step 1: Prepare a 2% silane coupling agent ethanol aqueous solution, soak and stir the microspheres for 20 min, dry at 100℃ for 2 h, and perform surface modification treatment; Step 2: Preheat the epoxy resin to 50°C, add the ceramic hollow microspheres and stir at low speed until uniform, then add the cycloaliphatic amine curing agent and stir for 3 minutes; Step 3: Place the well-stirred mixture into the mold, pre-cur at 50℃ for 2 hours to remove bubbles, then heat to 90℃ and maintain the temperature for 6 hours to cure. Finally, allow it to cool naturally to solidify and demold.
[0035] Based on the above preparation method, test strips were prepared by selecting different raw material ratios. The specific experimental ratios and performance data are as follows (bisphenol A epoxy resin = 100 parts by weight). Based on the above test results, it can be seen that after adding ceramic hollow microspheres to the epoxy resin matrix, the material density is between 0.4 and 0.5 g / cm³, and the compressive strength exceeds 55 MPa, meeting the high-pressure load-bearing requirements of deep-sea applications. Furthermore, the water absorption rate in the high-pressure immersion test is less than 0.5%, and the buoyancy loss rate is less than 2%. Compared with traditional glass microsphere epoxy materials, the structural stability under high-pressure conditions is significantly improved, making it fully suitable for the use requirements of deep-sea buoyancy blocks, underwater oil and gas pressure-resistant components, and other equipment. Example 3
[0036] The ceramic hollow microsphere composite material was prepared using G-grade oil well cement, aluminosilicate ceramic hollow microspheres, polycarboxylate dispersant, acrylamide water loss reducer, and lignin sulfonate retarder. The preparation steps are as follows. Step 1: Mechanically dry mix G-grade oil well cement, aluminum silicate ceramic hollow microspheres, polycarboxylate dispersant, acrylamide water loss reducer, and lignin sulfonate retarder for 5 minutes; Step 2: Control the water-cement ratio to 0.45, add water, and mix at high speed for 5 minutes to prepare a uniform slurry; Step 3: Let stand at room temperature for 2 hours to prepare composite cement slurry.
[0037] Based on the above preparation method, different raw material ratios were selected to prepare test slurries, which were then cured at a constant temperature in a 50MPa high-pressure curing autoclave for 72 hours to obtain hardened cement samples. The specific experimental ratios and performance data are as follows (G-grade oil well cement = 100 parts by weight). The above test results show that adding ceramic hollow microspheres to cement as a matrix reduces density by 25%–35% and improves overall slurry fluidity by 30%–40%, resulting in excellent workability. After long-term curing under 50MPa high pressure, the compressive strength retention rate is higher than 95%, and the material structure remains intact with minimal degradation of mechanical properties under high pressure. Combining the advantages of lightweight, easy construction, and high-pressure durability, it can be used for long-term application in deep well high-pressure cementing sheaths, solving the problem of high-pressure failure of traditional lightweight cement.
[0038] In summary, the ceramic hollow microsphere composite material of this application has the following technical advantages compared with the prior art: 1. This invention addresses the shortcomings of traditional microspheres, such as insufficient pressure resistance and susceptibility to structural failure, significantly improving the material's stability under high pressure. It utilizes hollow ceramic microspheres, overcoming the limitations of hollow glass microspheres (compressive strength less than 30 MPa, prone to crushing under high pressure) and polymer microspheres (low strength, unable to bear loads). Furthermore, compared to ordinary single-component ceramic microspheres, this invention, through material selection and parameter limitation, maintains ultra-high structural stability while ensuring extremely low density. When applied to harsh conditions such as deep-sea high pressure and deep well cementing, it effectively avoids microsphere collapse and the failure of the lightweight properties of composite materials, significantly extending the material's pressure-bearing service life.
[0039] 2. Existing technologies lack a compatibility system for different matrices and ceramic microspheres, resulting in problems such as chaotic material selection and low performance utilization. This invention establishes a targeted matching system: mullite and alumina silicate hollow microspheres are preferred for the polyamide matrix; alumina and zirconia hollow microspheres are preferred for the epoxy resin matrix; and mullite and alumina silicate hollow microspheres are suitable for the cement matrix. Combined with a surface modification process using a coupling agent, this effectively improves the mismatch between the surface polarity of the ceramic microspheres and the compatibility with the matrix, eliminates defects such as interfacial debonding and weak bonding, and maximizes the mechanical, heat-resistant, and stable performance advantages of ceramic microspheres made of different materials.
[0040] 3. Solved the common molding problems of hollow microsphere composite systems. For polyamide injection molding systems, it avoids the problems of air bubbles and warping caused by gas generation from microspheres, achieving defect-free molding of products; for epoxy resin systems, the closed-cell structure of microspheres combined with optimized formulation results in extremely low water absorption and buoyancy loss rates, structural stability under high pressure holding, and excellent water-proof and seepage-proof performance; for cement systems, the dispersion is optimized through additive compounding, solving the problems of microsphere floating, settling, and uneven dispersion, improving the overall uniformity and construction stability of cement-based composite materials.
[0041] 4. It overcomes the limitations of traditional microsphere composite materials, such as low temperature resistance, pressure difference resistance, weak stability, and limited applicability. The material simultaneously possesses multiple advantages, including lightweight, high strength, high temperature resistance, high pressure resistance, low water absorption, and good chemical stability. It can be precisely adapted to high-end and demanding applications such as lightweight automotive structural components, deep-sea pressure-resistant buoyancy components at depths of 10,000 meters, deep-sea oil and gas extraction equipment, and high-pressure cementing sheaths for deep wells. This solves the industry problem of existing materials being unable to meet the performance requirements of multiple extreme working conditions, demonstrating extremely high engineering application value and industrialization prospects.
[0042] 5. Using ceramic hollow microspheres as the only microsphere filler eliminates the need for mixed systems with multiple fillers. The formula is simple and the components are controllable. At the same time, it is matched with exclusive molding processes for different matrices such as resin and cement, which has strong process compatibility and high production stability. It avoids the problems of complex composition, difficult process and high cost of traditional composite systems, and is convenient for large-scale industrial production.
[0043] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Any other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention, as long as they do not depart from the direction and scope of the technical solutions of the present invention, should be covered within the scope of the claims of the present invention.
Claims
1. A ceramic hollow microsphere composite material, characterized in that: The product comprises a matrix material and hollow ceramic microspheres, wherein the hollow ceramic microspheres are uniformly dispersed and mixed in the matrix material. The hollow ceramic microspheres are one or a combination of alumina hollow ceramic microspheres, zirconia hollow ceramic microspheres, mullite hollow ceramic microspheres, and aluminum silicate hollow ceramic microspheres. The matrix material is any one of polyamide resin, epoxy resin, or cement. The particle size D50 of the hollow ceramic microspheres is 10–100 μm.
2. The ceramic hollow microsphere composite material according to claim 1, characterized in that: When the matrix material is polyamide resin, it comprises 18-22 parts of ceramic hollow microspheres, 0.5-2 parts of coupling agent, and 0.1-1 parts of antioxidant per 100 parts by weight of polyamide resin; the ceramic hollow microspheres are mullite ceramic hollow microspheres or aluminosilicate ceramic hollow microspheres.
3. The ceramic hollow microsphere composite material according to claim 1, characterized in that: When the matrix material is epoxy resin, it comprises 33-38 parts of ceramic hollow microspheres and 2-5 parts of curing agent per 100 parts by weight of epoxy resin; the ceramic hollow microspheres are alumina ceramic hollow microspheres, zirconia ceramic hollow microspheres, or a combination thereof.
4. The ceramic hollow microsphere composite material according to claim 1, characterized in that: When the matrix material is cement, it comprises 22-28 parts of ceramic hollow microspheres, 0.5-1.5 parts of dispersant, 0.5-2 parts of water loss reducing agent, and 0.1-1 parts of retarder per 100 parts by weight of cement; the ceramic hollow microspheres are mullite or aluminosilicate ceramic hollow microspheres.
5. The ceramic hollow microsphere composite material according to claim 1, characterized in that: The ceramic hollow microspheres are surface modified by a coupling agent, which is a silane coupling agent, a titanate coupling agent, or an aluminate coupling agent.
6. The ceramic hollow microsphere composite material according to any one of claims 2-4, characterized in that: The polyamide resin is PA66, PA12, or PA46; the epoxy resin is bisphenol A type epoxy resin, bisphenol F type epoxy resin, or phenolic epoxy resin; the cement is G-grade oil well cement, H-grade oil well cement, or silicate cement.
7. The method for preparing ceramic hollow microsphere composite materials according to claims 1-6, characterized in that: Includes the following steps, Step 1: Surface modification treatment of ceramic hollow microspheres; Step 2: Mix the modified ceramic hollow microspheres with the matrix material and additives evenly; Step 3: Depending on the type of base material, molding is carried out by melt blending injection molding, pouring curing, or water mixing and curing.
8. The method for preparing ceramic hollow microsphere composite material according to claim 7, characterized in that: When the matrix material is polyamide resin, a twin-screw extruder is used for melt blending, the barrel temperature is 200-300℃, and ceramic hollow microspheres are added by side feeding for injection molding; when the matrix material is epoxy resin, casting molding is used and cured at room temperature to 120℃; when the matrix material is cement, water is added at a water-cement ratio of 0.3-0.6, stirred, and then injected into the mold for curing.
9. The method for preparing ceramic hollow microsphere composite material according to claim 7, characterized in that: The surface modification treatment in step one involves preparing a 1-4 wt% coupling agent ethanol aqueous solution, soaking and stirring the ceramic hollow microspheres for 15-25 min, and then drying them at 90-110℃ for 1.5-2.5 h.